2016
DOI: 10.1111/jcpt.12376
|View full text |Cite
|
Sign up to set email alerts
|

A change in the trend in dosulepin usage following the introduction of a prescribing indicator but not after two national safety warnings

Abstract: The trend in dosulepin usage in Wales altered significantly following the introduction of the NPI, but not after the other prescribing advice. This association, coupled with the absence of a significant change in NE England over the same period, provided some evidence of the effectiveness of the NPI in prompting a change in prescribing behaviour in Wales.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…Of 11 466 identified articles, 40 studies examining UK medicines regulatory risk communications were included (Figure S1). These 40 studies examined the impact of 25 UK regulatory risk communications. Twelve of the 25 risk communications recommended a restriction of or change in medicine indication, 8 asked prescribers to be aware of new information about safety without explicit recommendations for action, 4 related to product withdrawals, and 1 to both restriction of indication and additional monitoring (Table and Table S1).…”
Section: Resultsmentioning
confidence: 99%
“…Of 11 466 identified articles, 40 studies examining UK medicines regulatory risk communications were included (Figure S1). These 40 studies examined the impact of 25 UK regulatory risk communications. Twelve of the 25 risk communications recommended a restriction of or change in medicine indication, 8 asked prescribers to be aware of new information about safety without explicit recommendations for action, 4 related to product withdrawals, and 1 to both restriction of indication and additional monitoring (Table and Table S1).…”
Section: Resultsmentioning
confidence: 99%
“…The trend in dosulepin usage in Wales altered significantly (downwards) following the introduction of the NPI. This association, and the observation of no significant change in North‐East England over the same period, suggested that the NPI and associated focus on the issue may have contributed to the effect seen 26 …”
Section: Resultsmentioning
confidence: 88%
“…Prescribing indicators have been used in the NHS for over 30 years to measure the quality and effectiveness of prescribing in GP. 19 20 Although there is some evidence of the effectiveness of the role of prescribing indicators in supporting improving quality in prescribing 21 particularly where they form part of multifaceted interventions, 22 23 they have been most commonly used to monitor changes in prescribing behaviour and cost over time. 24 Being shown to be an outlier can be an ‘eye opener’ and highlight priority areas for local action to change prescribing behaviour and improve quality.…”
Section: Resultsmentioning
confidence: 99%